Exploring the plastid genome disparity of liverworts. Issue 4 (9th August 2019) - Yu, Ying; Liu, Hong‐Mei; Yang, Jun‐Bo; Ma, Wen‐Zhang; Pressel, Silvia; Wu, Yu‐Huan; Schneider, Harald
Abstract: Sequencing the plastid genomes of land plants provides crucial improvements to our understanding of the plastome evolution of land plants. Although the number of available complete plastid genome sequences has rapidly increased in the recent years, only a few sequences have been yet released for the three bryophyte lineages, namely hornworts, liverworts, and mosses. Here, we explore the disparity of the plastome structure of liverworts by increasing the number of sequenced liverwort plastomes from five to 18. The expanded sampling included representatives of all major lineages of liverworts including the genus Haplomitrium . The disparity of the liverwort genomes was compared with other 2386 land plant plastomes with emphasis on genome size and GC‐content. We found evidence for structural conservatism of the plastid genomes in liverworts and a trend towards reduced plastome sequence length in liverworts and derived mosses compared to other land plants, including hornworts and basal lineages of mosses. Furthermore, Aneura and Haplomitrium were distinct from other liverworts by an increased GC content, with the one found in Haplomitrium only second to the lycophyte Selaginella . The results suggest the hypothesis that liverworts and other land plants inherited and conserved the plastome structure of their most recent algal ancestors.